The impact of gestational age limits on abortion-related outcomes: a synthesis of legal and health evidence - Fiona de Londras; Amanda Cleeve; Maria I. Rodriguez; Alana Farrell; Magdalena Furgalska; Antonella F. Lavelanet (BMC Global and Public Health)
Abstract Background Gestational age limits (GLs) are common in abortion laws and policies. They restrict when lawful abortion may be accessed by reference to the gestational duration of a pregnancy, in some cases specifying that abortion is a criminal offense after, but not before, the GL. This synthesis of legal and health evidence addresses knowledge gaps on the health and non-health outcomes plausibly related to the effects of GLs on abortion-related outcomes. Methods This paper synthesizes the results of a systemic review with the identification and application of relevant international human rights standards. A search strategy was drawn up to capture public health, international human rights law, and policy evidence related to the impacts of GLs. We limited our search to papers published in English since 2010, including quantitative studies (comparative and non-comparative), qualitative and mixed-methods studies, reports, PhD theses, and economic or legal analyses. Only studies that undertook original data collection or analysis were included. Review of treaties, opinions, interpretations, general comments, and special procedures of UN human rights bodies identified relevant human rights standards, which were then synthesized with the extracted data to create a comprehensive evidence synthesis. Results GLs do not prevent people from seeking abortion but do operate as a regulatory barrier that can result in people seeking abortion outside of the formal health system or unwillingly continuing pregnancy. In many jurisdictions, they interact with the criminalization of abortion, with significant health and non-health impacts. GLs impact most on people who are least able to access abortion because of later detection of pregnancy, lack of access to abortion provision, and lack of access to the resources required to avail of abortion. Conclusions Although paradigmatic in abortion law, GLs are not based on evidence of either the safety or effectiveness of abortion or the needs and preferences of pregnant people. They produce rights-limiting impacts for pregnant people and, in some cases, result in arbitrary and disproportionate violations of legally protected rights. The persistence of GLs as part of the regulatory framework for abortion provision cannot be said to ensure an enabling environment for quality abortion care.